Simulated learning environment (SLE) in audiology education: a systematic review - Dzulkarnain, Ahmad Aidil Arafat; Wan Mohd Pandi, Wan Mahirah; Rahmat, Sarah; Zakaria, Nur 'Azzah (2015)
There are various types of SLE tool that have been described and developed since the 1970s in the field of audiology. These SLE tools include those for basic audiometry testing, auditory brainstem response waveform analysis, simulated patients for examination and simulated patients for counselling. With this development, many countries are now focusing on research in audiology education by either implementing or piloting the use of SLE training in their audiology curriculum. The objective of this study is to systematically review the relevant previous literature investigating the outcome of Simulated Learning Environment (SLE) training in audiology education. A systematic review research design was used and fifteen databases were searched using various relevant keywords. Based on the analysis, three of the four selected studies revealed positive findings for the use of an SLE. The SLEs group showed higher post-training score compared to the traditional training group or significantly higher post-training score than the non-training groups. One study on the other hand revealed negative findings, where the traditional training group showed significantly higher post-training score than the SLE group. In addition, two studies reported significant improvement after SLE training with the post-training scores were significantly higher than the pre-SLE-training scores. Overall, this review supports the notions that SLE training can be an effective learning tool and can be used for basic clinical training. This conclusion should be treated with caution considering the limited numbers of studies published in this area, exalting more SLE researches to be conducted in the future.